A review of reactive power sharing control techniques for islanded microgrids. (May 2021) - Rosini, A.; Labella, A.; Bonfiglio, A.; Procopio, R.; Guerrero, Josep M.
Abstract: The paper presents a review of the approaches developed to solve the problem of primary voltage control and reactive power sharing ( Q/V primary control) among converter interfaced production units present in a microgrid. First of all, a general survey of the methods is proposed with specific focus on communication-less methods that are surely the most challenging. Then, the article focuses on a detailed comparison of state-of-the-art communication-less approaches such as droop control (the most widely adopted) and three more recent alternative methods. A comparative analysis is performed by means of dedicated simulations on a common benchmark network in different operational and topological set-ups to highlight their advantages and drawbacks. The main result of this comparison is that the new methods are all improvements to the traditional droop technique, but network configuration and parameters have a great impact on the method performances and so a univocal ranking among them is not possible. Therefore, the issue of designing an effective Q/V primary controller for microgrids is still a partly open issue which requires further investigation and research. Highlights: Reactive power control techniques for islanded microgrids. Detail state-of-the art analysis of communication-less techniques. Comparative analysis on a common testcase microgrid of state-of-the-art techniques.